Moving in musicking: the evolving pedagogical practice of the artist-facilitator within asylum seeker centers - Nicolaou, Georgia; Nijs, Luc; van Petegem, Peter (Frontiers in Psychology, 2023)
The field of community music has been continuously expanding during the last years alongside the need for experienced musicians who can carry out music activities for culturally diverse groups. Based on previous studies, we identified a need for research-based practices for training musicians and music teachers who wish to facilitate community music projects. We believe that it is important to incorporate reflexive practice in order to inform the planning of the workshops, but also to support the needs of the participants. The article examines the evolution of the pedagogical practice of the artist-facilitator in active music making with children, during a series of movement-based musical workshops at an asylum seeker center in the Netherlands. We used an exploratory case study integrating Action Research, in order to focus on the artist-facilitator’s pedagogical practice, the participatory role of the children and the content of this type of workshops. The researchers describe the adopted pedagogical approach based on a set of guiding principles and key components that supported the design and content of the workshops. Based on a cyclical process (plan-act-observe-evaluate), the findings from every cycle were incorporated in the next one by analyzing the video footage of the workshops and the immediate reflections of the artist-facilitator. Data analysis revealed a set of recurring themes that reflect crucial aspects of the artist-facilitator’s practice. Furthermore, a set of pedagogical implications are proposed that can be directly implemented to the practice of artists-facilitators who wish to engage in activities with children at asylum seeker centers.